Effects of preexercise carbohydrate ingestion on mountain bike performance - Cramp, T.; Broad, E.; Martin, D.; Meyer, B. J. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: This study examined the performance and metabolic effects of consuming 1.0 (LC) and 3.0 (HC) grams of carbohydrate (CHO) per kilogram body mass (BM), 3 h before a 93-min simulated mountain bike race. METHODS: After two familiarization trials, eight male subjects undertook two CHO trials in a double-blind counterbalanced fashion on a cycle ergometer. The HC meal was supplemented with maltodextrin while maintaining the same glycemic index and apparent volume of food as the LC meal. Stochastic cycling was undertaken for 93 min (4 x 22.50-min laps) with performance measured as the total work performed in 6 x 30-s periods each lap during the test. RESULTS: Performance in lap 1 was better with LC (P < 0.03) whereas performance in lap 4 was better with HC (P < 0.02). Overall performance was 3% greater in HC compared with LC (NS, P = 0.13). Serum glucose was significantly lower (P < 0.04) in HC immediately before the mountain bike test (180 min postprandial) and at 10 min into the test (P < 0.01). Gastrointestinal comfort decreased similarly for both trials over time (P < 0.05). CONCLUSION: These data suggest that ingestion of 3.0 g x kg(-1) BM of CHO 3 h before a 93-min mountain bike simulated race does not produce a statistically significant improvement in overall performance compared with 1.0 g x kg(-1) BM. However, in real terms, a 3% performance improvement may benefit athletes in a race situation. Differences in performance during the first and last laps indicate a variation in pacing strategies that may have resulted from differing blood glucose levels between trials.